Precursor sheet for fuel cell separator, and fuel cell separator

JP2025033946AActive Publication Date: 2025-03-13NISSHINBO CHEM
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023140012
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13
Estimated Expiration
2043-08-30

AI Technical Summary

Benefits of technology

【0010】 本発明の燃料電池セパレータ用前駆体シートは、良好な強度を有するとともに、水性溶媒で再スラリー化することができ、製造時の不良品や、加工時の端材を再スラリー化して再びシート状に加工し直すことができるため、製造時のロスを削減することができる。 また、本発明の燃料電池セパレータ用前駆体シートを用いて得られた燃料電池セパレータは、導電性およびガス不透過性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033946000001
    Figure 2025033946000001
  • Figure 2025033946000002
    Figure 2025033946000002
  • Figure 2025033946000003
    Figure 2025033946000003
Patent Text Reader

Abstract

To provide a precursor sheet for a fuel cell which can be re-processed into slurry in an aqueous solvent, thereby enabling recycling of defectives and end materials generated in processing and giving a separator that has good strength, low volume resistivity and high gas impermeability.SOLUTION: A precursor sheet for a fuel cell separator contains black particles, a particulate or fibrous water-insoluble resin and a water-soluble resin, wherein a content of the water-soluble resin is 0.8 to 18.0 pts.mass with respect to 100 pts.mass of the black particles, and a content of the particulate or fibrous water-insoluble resin is 19.0 to 63.0 pts.mass with respect to 100 pts.mass of the black particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a precursor sheet for a fuel cell separator and a fuel cell separator. [Background technology]

[0002] The fuel cell separator serves to provide electrical conductivity to each unit cell, ensure passage of fuel and air (oxygen) supplied to the unit cells, and act as a boundary wall separating them. Generally, properties required for fuel cell separators include gas (hydrogen and oxygen) impermeability, electrical conductivity, mechanical strength, durability (heat resistance, water resistance, acid resistance), thin and lightweight, and formability.

[0003] A conventional method for producing such fuel cell separators is to heat and compress a sheet-like separator precursor. For example, Patent Document 1 discloses a fuel cell separator comprising a conductive base sheet, a dense layer containing first graphite particles having a predetermined bulk density and volume resistivity (conductivity), and a conductive layer containing second graphite particles having a predetermined bulk density and volume resistivity, the dense layer and the conductive layer being obtained by compression molding a precursor sheet for a fuel cell separator containing a resin. Patent document 2 discloses a fuel cell separator obtained by thermoforming a stampable sheet containing a conductive filler and a polymeric material in a molding machine equipped with a pair of dies engraved with the shape of a fuel cell separator.

[0004] Thus, although there have been many separator manufacturing techniques using sheet-shaped precursors, there has been no known means for easily reusing the sheet-shaped precursors in an aqueous solvent (by forming a slurry). For example, Patent Document 1 discloses that the above-mentioned conductive layer can be produced using a conductive layer-forming composition containing a water-soluble resin as a binder, graphite, and a resin. However, since the conductive layer is impregnated with a non-water-soluble resin liquid dissolved in a solvent, the non-water-soluble resin liquid coats the graphite and causes the graphite to adhere, making it difficult to re-dissolve it in an aqueous solvent or re-slurry it for reuse. Patent Document 2 also uses a stampable sheet manufactured by a paper-making method from a suspension containing a conductive filler and a polymer material. However, when the sheet is made, it is dried at high temperature and then pressed. This causes the polymer particles to adhere to each other and to the polymer material and the conductive filler, making it difficult to re-dissolve the sheet in an aqueous solvent or re-slurry it for reuse. Furthermore, none of the documents mentions anything about reusing the sheet-like precursor. Furthermore, separators obtained from conventional sheet-like precursors have poor electrical conductivity because an insulating layer of water-insoluble resin is easily formed between the graphite particles on the surface and on the surface of the graphite particles. In order to increase electrical conductivity, it is necessary to reduce the amount of resin added, making it difficult to achieve both this and gas impermeability.

[0005] Furthermore, Patent Document 3 discloses a coating composition for use in a current collector plate with a coating layer for a fuel cell, which contains a carbon material, a water-soluble resin binder, a water-dispersible resin particulate binder, and an aqueous liquid medium, and Patent Document 4 discloses a coating composition for use in a separator with a coating layer for a fuel cell, which contains a carbon material, a water-soluble resin binder, a water-dispersible resin particulate binder, and an aqueous liquid medium. However, the compositions of Patent Documents 3 and 4 are coating compositions for coating the surfaces of current collectors or separators, and are not precursor sheets for fuel cell separators. Furthermore, the above coating compositions are not only not formed into a sheet to be used as separator precursors, but also cannot be reused by redissolving in an aqueous solvent or reslurrying, since they form a water-resistant coating film after application and drying. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 7056796 [Patent Document 2] JP 2006-269313 A [Patent Document 3] JP 2016-183325 A [Patent Document 4] JP 2016-81717 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above circumstances, and aims to provide a precursor sheet for a fuel cell and a fuel cell separator which can be reslurried in an aqueous solvent, thereby enabling reuse of defective products and scraps generated during processing, and which provides a separator having good strength, electrical conductivity and gas impermeability. [Means for solving the problem]

[0008] As a result of extensive research into achieving the above-mentioned object, the inventors discovered that a precursor sheet for a fuel cell separator, which contains graphite particles, a particulate or fibrous water-insoluble resin, and a water-soluble resin in predetermined proportions, can be reslurried in an aqueous solvent, thereby making it easy to reuse defective products and scraps generated during processing, and providing a separator which has good strength and is highly conductive and gas impermeable, thereby completing the present invention.

[0009] That is, the present invention provides 1. A material containing graphite particles, particulate or fibrous water-insoluble resin, and water-soluble resin; the content of the water-soluble resin is 0.8 to 18.0 parts by mass relative to 100 parts by mass of the graphite particles, a precursor sheet for a fuel cell separator, characterized in that the content of the particulate or fibrous water-insoluble resin is 19.0 to 63.0 parts by mass per 100 parts by mass of the graphite particles; 2. The fuel cell separator precursor sheet according to 1, wherein the content of the water-soluble resin is 1.0 to 16.0 parts by mass per 100 parts by mass of the graphite particles. 3. The fuel cell separator precursor sheet according to claim 1, wherein the content of the particulate or fibrous water-insoluble resin is 20.0 to 60.0 parts by mass per 100 parts by mass of the graphite particles. 4. A precursor sheet for a fuel cell separator according to claim 1, wherein the graphite particles and the particulate or fibrous water-insoluble resin are fixed by the water-soluble resin. 5. A precursor sheet for a fuel cell separator according to claim 1, comprising carbon fibers. 6. A fuel cell separator obtained by molding the fuel cell separator precursor sheet according to any one of 1 to 5. to provide. Effect of the Invention

[0010] The precursor sheet for a fuel cell separator of the present invention has good strength and can be reslurried in an aqueous solvent, so that defective products during production and scraps from processing can be reslurried and reprocessed into a sheet form, thereby reducing losses during production. Furthermore, a fuel cell separator obtained by using the fuel cell separator precursor sheet of the present invention has excellent electrical conductivity and gas impermeability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in further detail below. The precursor sheet for a fuel cell separator according to the present invention (hereinafter abbreviated as "precursor sheet") contains graphite particles, a particulate or fibrous water-insoluble resin, and a water-soluble resin, and is characterized in that the content of the water-soluble resin is 0.8 to 18.0 parts by mass per 100 parts by mass of the graphite particles, and the content of the particulate or fibrous water-insoluble resin is 19.0 to 63.0 parts by mass per 100 parts by mass of the graphite particles.

[0012] [1] Graphite particles The graphite particles constituting the precursor sheet of the present invention are not particularly limited, and either natural graphite or artificial graphite may be used. The artificial graphite particles can be appropriately selected from those conventionally used in fuel cell separators, specific examples of which include artificial graphite obtained by calcining needle coke, artificial graphite obtained by calcining lump coke, and the like. On the other hand, the natural graphite particles may be appropriately selected from those conventionally used in fuel cell separators, specific examples of which include lump natural graphite and flake natural graphite. These graphite particles may be used alone or in combination of two or more kinds.

[0013] The shape of the graphite particles is not particularly limited, but from the viewpoint of electrical conductivity, a spherical or flaky shape is preferred. The average particle size of the graphite particles is not particularly limited, but in consideration of increasing the electrical conductivity, it is preferably 5 to 200 μm, more preferably 10 to 200 μm, even more preferably 10 to 100 μm, and even more preferably 10 to 50 μm. In the present invention, the average particle size is the median diameter (d 50 ) (hereinafter the same).

[0014] [2] Particulate or fibrous water-insoluble resin The particulate or fibrous water-insoluble resin is not particularly limited as long as it is particulate or fibrous and does not dissolve in water, and may be a thermoplastic resin or a thermosetting resin. As the thermoplastic resin, a resin having a melting point or glass transition point of 100° C. or higher is preferred, because it has heat resistance that allows the resin to maintain a particulate or fibrous form during drying in producing the precursor sheet. Specific examples thereof include polyethylene, polypropylene, polyphenylene sulfide, polytetrafluoroethylene, tetrafluoroethylene-ethylene copolymer, polychlorotrifluoroethylene, polyamide, polyetherketoneetherketoneketone, polyetherketone, liquid crystal polymer, polyimide, polyamideimide, polyphenylsulfone, polyetherimide and polysulfone, polybutylene terephthalate, polyethylene naphthalate, ABS resin, polycycloolefin and polyethersulfone, and derivatives thereof having a melting point of 100° C. or higher, polycarbonate, polystyrene and polyphenylene oxide, and derivatives thereof having a glass transition point of 100° C. or higher, which may be used alone or in combination of two or more. The upper limit of the melting point or glass transition point is not particularly limited, but from the viewpoint of productivity of the precursor sheet and fuel cell separator, it is preferable that it is 300° C. or lower.

[0015] The thermosetting resin can be appropriately selected from those that have been conventionally used as binder resins for carbon separators and the like. Specific examples thereof include phenolic resins, epoxy resins, furan resins, unsaturated polyester resins, urea resins, melamine resins, diallyl phthalate resins, bismaleimide resins, polycarbodiimide resins, silicone resins, vinyl ester resins, benzoxazine resins, etc., which may be used alone or in combination of two or more. Among these, epoxy resins and phenolic resins are preferred because of their excellent heat resistance and mechanical strength. These water-insoluble resins are commercially available.

[0016] The particle shape of the water-insoluble resin is not particularly limited and may be any shape such as spherical, scale-like, block-like, foil-like, plate-like, needle-like, amorphous, etc., but from the viewpoint of particle packing, a spherical shape is preferred. The average particle size of the water-insoluble resin is not particularly limited, but is preferably 1 to 150 μm from the viewpoints of increasing the packing properties of the particles and reducing the resistance of the resulting fuel cell separator.

[0017] In the precursor sheet of the present invention, the content of the particulate or fibrous water-insoluble resin is 19.0 to 63.0 parts by mass per 100 parts by mass of graphite particles. In order to improve the strength, gas impermeability, and conductivity of the resulting fuel cell separator, the content is preferably 20.0 to 60.0 parts by mass, more preferably 21.0 to 59.0 parts by mass, and even more preferably 25.0 to 38.0 parts by mass per 100 parts by mass of graphite particles.

[0018] [3] Water-soluble resin The water-soluble resin preferably has dispersibility, viscosity increasing properties, and adhesive properties from the viewpoint of uniformly dispersing the graphite particles and the particulate or fibrous water-insoluble resin to form a sheet. In the present invention, "water-soluble" means that the resin is completely dissolved in water at 25°C at a concentration of at least 1% by mass. Specific examples of the water-soluble resin include aqueous resins such as acrylic resins, polyvinyl resins, polyether resins, polyurethane resins, polyester resins, polyolefin resins, polyamide resins, polyimide resins, polyallylamine resins, phenol resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, formaldehyde resins, silicone resins, fluororesins, and polysaccharides such as carboxymethylcellulose, which may be used alone or in combination of two or more. Among these, from the viewpoint of uniformly dispersing graphite particles and particulate or fibrous water-insoluble resins and forming them into a sheet with a particularly small amount of addition, acrylic resins, polyvinyl resins, polyether resins, and polysaccharides such as carboxymethylcellulose are preferred. These water-soluble resins are commercially available.

[0019] In the precursor sheet of the present invention, the content of the water-soluble resin is 0.8 to 18.0 parts by mass relative to 100 parts by mass of the graphite particles. In consideration of improving the dispersibility of the slurry for producing the precursor sheet, the strength and ease of reslurrying of the precursor sheet, and the electrical conductivity of the resulting fuel cell separator, the content is preferably 1.0 to 16.0 parts by mass, more preferably 2.0 to 16.0 parts by mass, and even more preferably 2.0 to 15.5 parts by mass relative to 100 parts by mass of the graphite particles.

[0020] [4] Other ingredients The precursor sheet of the present invention may contain, in addition to the components described above, other components that are typically used in fuel cell separators. Other components include internal release agents such as stearic acid wax, amide wax, montanic acid wax, carnauba wax, and polyethylene wax, conductive assistants such as carbon black, and reinforcing materials such as carbon fiber. In particular, from the viewpoint of further improving the strength of the precursor sheet and the separator, it is preferable to contain carbon fiber. From the viewpoint of improving reslurry of the precursor sheet, the content of the other components is preferably 0.1 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the graphite particles.

[0021] [5] Manufacturing method of precursor sheet The precursor sheet of the present invention can be obtained, for example, by dispersing a composition containing graphite particles, a particulate or fibrous water-insoluble resin, and a water-soluble resin in water to prepare a precursor sheet, forming the slurry into a sheet by coating or casting, and then drying and removing the water. In this way, by uniformly dispersing graphite and a particulate or fibrous water-insoluble resin by wet kneading and forming the sheet, it is possible to suppress the generation of voids due to unfilled resin during heat compression molding, and to obtain a separator with higher gas impermeability.

[0022] An example of a method for producing a precursor sheet by coating is a method for coating a resin film such as a PET film with a slurry, drying the slurry, and then peeling the slurry from the resin film. The coating method is not particularly limited, and may be appropriately selected from known methods such as spin coating, dip coating, flow coating, inkjet coating, jet dispenser coating, spray coating, bar coating, gravure coating, roll coating, transfer printing, brush coating, blade coating, air knife coating, die coating, and screen printing.

[0023] An example of a method for producing a precursor sheet by casting is to pour the slurry into a box-shaped mold, dry it, and then remove it from the mold. If a mold with a shape that reflects the irregularities of the separator is used in advance, a precursor sheet with partially different thicknesses, which is difficult to produce by a coating method, can be produced. The material of the mold is not particularly limited, and may be appropriately selected from known materials such as a release-treated metal mold or a plastic mold made of silicone, fluororesin, or the like.

[0024] The drying temperature for the slurry is not particularly limited as long as it is below the melting point or glass transition point of the particulate or fibrous water-insoluble resin, but is preferably below 100°C, more preferably from room temperature to 100°C, and even more preferably from 50 to 100°C. The thickness of the precursor sheet is not particularly limited as long as it allows the production of a fuel cell separator, but is preferably from 100 μm to 1 mm, and more preferably from 200 to 800 μm.

[0025] The precursor sheet of the present invention is a sheet of graphite particles and particulate or fibrous water-insoluble resin formed by the water-soluble resin, and although its form is not particularly limited, it is preferable that at least a portion of it has a structure in which graphite particles and particulate or fibrous water-insoluble resin are fixed by the water-soluble resin.

[0026] The precursor sheet of the present invention has the characteristic that its shape is maintained by the dried water-soluble resin and has the strength to be handled in sheet form, while the water-soluble resin redissolves when it comes into contact with water, making it easy to form a slurry. Furthermore, since the slurry can be made into a sheet simply by drying and removing the water, it is easy to make a precursor sheet having an uneven shape with different thicknesses, rather than simply a flat plate shape as in the conventional method.

[0027] [5] Fuel cell separator The precursor sheet of the present invention can be heated and molded to produce a fuel cell separator. The molding method is not particularly limited, but compression molding is preferred. The temperature during compression molding is not particularly limited as long as it exceeds the melting point or glass transition point of the particulate or fibrous water-insoluble resin, but a mold temperature of 150 to 250°C is preferred. The molding pressure is preferably from 1 to 100 MPa, and more preferably from 1 to 60 MPa. The compression molding time is not particularly limited and can be appropriately set within a range from about 3 seconds to 1 hour.

[0028] By subjecting the precursor sheet of the present invention to heat compression molding, a separator of a desired shape can be obtained by melting a particulate or fibrous water-insoluble resin to fill voids and bond the graphite particles together. In the precursor sheet of the present invention, a particulate or fibrous water-insoluble resin is used, so that the graphite particles are not coated with a water-insoluble resin in advance as in the past, and it is possible to suppress the formation of a resin layer on the separator surface during compression molding, resulting in low contact resistance and penetration resistance and excellent electrical conductivity, and in addition, the resin content can be increased, resulting in a separator with high gas impermeability. In particular, since the formation of a resin layer on the separator surface is suppressed, the step of removing the resin layer to improve electrical conductivity is unnecessary, and since the surface exposure rate of the graphite particles is increased, fine irregularities are formed, improving the adhesiveness of gaskets, etc., and further improving the releasability during hot compression molding.

[0029] Generally, a solid polymer electrolyte fuel cell is made up of a large number of unit cells arranged side by side, each unit cell being composed of a pair of electrodes sandwiching a solid polymer membrane and a pair of separators sandwiching these electrodes to form a gas supply and exhaust flow path. The fuel cell separator of the present invention can be used as some or all of these multiple separators. EXAMPLES

[0030] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0031] [1] Preparation of precursor sheet [Example 1-1] In terms of solid content ratio, 100 parts by mass of flake graphite (particle size 20 μm, same below), 7.1 parts by mass of polyacrylic acid (molecular weight 150,000, solid content concentration 25 mass% aqueous solution, same below) which is a water-soluble resin, 35.7 parts by mass of particulate phenolic resin (particle size 25 μm, molecular weight 10,000, same below) which is a particulate water-insoluble resin, and water as a solvent were mixed to prepare a slurry for producing a precursor sheet with a final solid content concentration of 50 mass%. The slurry was applied to a release-treated PET film using a bar coater, dried in a blower dryer at 80° C., and peeled off from the PET film to obtain a precursor sheet having a thickness of 480 μm.

[0032] [Example 1-2] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the particulate water-insoluble resin was changed from particulate phenolic resin to powdered polypropylene (particle size 15 μm).

[0033] [Examples 1-3] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 1.4 parts by mass, and the amount of particulate phenolic resin used was changed to 33.8 parts by mass.

[0034] [Examples 1-4] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 15.4 parts by mass, and the amount of particulate phenolic resin used was changed to 38.5 parts by mass.

[0035] [Examples 1-5] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 6.4 parts by mass, and the amount of particulate phenolic resin used was changed to 21.8 parts by mass.

[0036] [Examples 1-6] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 8.3 parts by mass, and the amount of particulate phenolic resin used was changed to 58.3 parts by mass.

[0037] [Examples 1-7] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 7.2 parts by mass, the amount of particulate phenolic resin used was changed to 36.1 parts by mass, and 1 part by mass of carbon fiber (φ7 μm, fiber length 6 mm) was further added.

[0038] [Examples 1-8] The precursor sheet obtained in Example 1-1 was mixed with water to prepare a slurry for producing a precursor sheet having a final solid concentration of 50% by mass. Except for using this slurry, a precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1.

[0039] [Comparative Example 1-1] A slurry was prepared in the same manner as in Example 1-1, except that the amount of particulate phenol resin used was changed to 33.3 parts by mass and polyacrylic acid was not added, but a precursor sheet could not be obtained.

[0040] [Comparative Example 1-2] In terms of solid content ratio, 100 parts by mass of flake graphite, 7.1 parts by mass of polyacrylic acid, and water were mixed to prepare a slurry with a final solid content concentration of 50% by mass. This slurry was applied to a release-treated PET film using a bar coater, dried in a blower dryer at 80°C, and peeled off from the PET film after drying to obtain a sheet. Particulate phenolic resin was dissolved in acetone solution to make a 50% by mass solution, and the previously prepared sheet was coated and impregnated with the solution to obtain a precursor sheet containing 5.7 parts by mass of non-particulate phenolic resin derived from particulate phenolic resin. The thickness of the obtained precursor sheet was 480 μm.

[0041] [Comparative Example 1-3] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 0.7 parts by mass.

[0042] [Comparative Example 1-4] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 19 parts by mass, and the amount of particulate phenolic resin used was changed to 39.7 parts by mass.

[0043] [Comparative Example 1-5] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 6.3 parts by mass, and the amount of particulate phenolic resin used was changed to 18.8 parts by mass.

[0044] [Comparative Example 1-6] A precursor sheet having a thickness of 480 μm was obtained in the same manner as in Example 1-1, except that the amount of polyacrylic acid used was changed to 8.6 parts by mass, and the amount of particulate phenolic resin used was changed to 63.8 parts by mass.

[0045] The above examples and comparative examples are summarized in Table 1.

[0046] [Table 1]

[0047] For the above Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-6, the dispersibility of the prepared slurries, the strength of the obtained precursor sheets, and the reslurry of the precursor sheets were evaluated by the following methods. The results are shown in Table 2. [Slurry Dispersibility] The presence or absence of streaks or defects during application of the PET film was visually confirmed, the thickness was measured at any six points, and the film was evaluated according to the following criteria. ◎: No streaks or defects, and the thickness variation of the obtained precursor sheet is less than 3% ◯: No streaks or defects, and the thickness variation of the obtained precursor sheet is 3% or more and less than 5% △: Streaks and defects cause unevenness, and the thickness variation of the obtained precursor sheet is 5% or more. ×: There are obvious streaks and defects and a precursor sheet cannot be obtained. [Strength of precursor sheet] The tensile strength of the precursor sheet was measured using an Autograph (manufactured by Shimadzu Corporation) at a chuck distance of 340 mm, a sample width of 40 mm, and a tensile speed of 100 mm / min to determine the strength at break. ◎: 20N / 40mm or more ○: 15N / 40mm or more, less than 20N / 40mm △: 10N / 40mm or more, less than 15N / 40mm ×: Less than 10N / 40mm [Reslurry] 30 g of the precursor sheet piece was added to 30 mL of water and stirred to re-form a slurry, and the presence or absence of streaks or defects upon application to the PET film was visually confirmed and evaluated according to the same criteria as for the dispersibility of the slurry described above. ◎: No streaks or defects, and the thickness variation of the obtained precursor sheet is less than 3% ◯: No streaks or defects, and the thickness variation of the obtained precursor sheet is 3% or more and less than 5% △: Streaks and defects cause unevenness, and the thickness variation of the obtained precursor sheet is 5% or more. ×: There are obvious streaks and defects and a precursor sheet cannot be obtained.

[0048] [Table 2]

[0049] [2] Fabrication of fuel cell separators [Example 2-1] The precursor sheet obtained in Example 1-1 was compression molded using a flat mold at 180° C. and 60 MPa for 5 minutes to obtain a fuel cell separator. The thickness of the separator molded in a flat shape was 250 μm.

[0050] [Example 2-2] The precursor sheet obtained in Example 1-2 was heated at 180°C for 10 minutes, and then cooled for 20 minutes while being compressed at 60 MPa using a flat mold to obtain a fuel cell separator. The thickness of the separator molded in a flat shape was 250 μm.

[0051] [Examples 2-3 to 2-8, Comparative Examples 2-1 to 2-6] A fuel cell separator was obtained in the same manner as in Example 2-1, except that the precursor sheets were changed to those prepared in Examples 1-3 to 1-8 and Comparative Examples 1-1 to 1-6.

[0052] The gas impermeability and electrical conductivity of the resulting fuel cell separator were measured by the following methods and evaluated according to the following criteria. The results are shown in Table 3. [Gas impermeability] A flat separator was molded and the hydrogen gas permeability coefficient (unit: cm) was measured in accordance with JIS K7126-1:2006 (Plastics and sheets - Gas permeability test method - Part 1: Differential pressure method). 3 cm / (cm 2 The measured values ​​were the pressure drop (MPa) and the temperature (cmHg) of the test gas (H2 gas) at 23°C and 150.3 kPa, respectively. ◎: Hydrogen gas permeability coefficient is 1.0×10 -10 cm 3 cm / (cm 2 Less than sec cmHg ○: Hydrogen gas permeability coefficient is 1.0×10 -10 m 3 cm / (cm 2 ·sec·cmHg) or more 1.0×10 -9 cm 3 cm / (cm 2 Less than sec cmHg △: Hydrogen gas permeability coefficient is 1.0×10 -9 cm 3 cm / (cm 2 ·sec·cmHg) or more 1.0×10 -8 cm 3 cm / (cm 2 ·sec·cmHg) ×: Hydrogen gas permeability coefficient is 1.0×10 -8 cm 3 cm / (cm 2 ·sec·cmHg) or more [Conductivity] A flat separator was molded and sandwiched between gold-plated copper electrodes with a side length of 2 cm. A pressure of 2.5 MPa was applied for 10 seconds, and then the pressure was reduced to 1.0 MPa. A current of 1 A / cm was applied between the gold-plated copper electrodes. 2 The interelectrode voltage was measured when a constant current of 1000 V was applied. The interelectrode voltage obtained was converted to resistance and used as the separator penetration resistance (unit: mΩ cm 2 ) and the conductivity was evaluated according to the following criteria. ◎: Piercing resistance is 8mΩ·cm 2 less than ○: Penetration resistance is 8mΩ·cm 2 More than 10mΩ cm 2 less than △: Penetration resistance is 10mΩ·cm 2 More than 15mΩ cm 2 less than ×: Penetration resistance is 15mΩ·cm 2 In the above case

[0053] [Table 3]

[0054] As shown in Tables 2 and 3, the precursor sheets of the respective Examples have good strength, can be reslurried, and provide separators that are both gas impermeable and electrically conductive. On the other hand, the slurry in Comparative Example 1-1 that did not contain polyacrylic acid as the water-soluble resin had poor dispersibility, and a precursor sheet could not be obtained. It is understood that the precursor sheet not containing particulate phenolic resin obtained in Comparative Example 1-2 (containing phenolic resin after dissolving in acetone) cannot be reslurried, and the separator obtained therefrom has poor electrical conductivity. It is apparent that the precursor sheet obtained in Comparative Example 1-3, in which the content of polyacrylic acid was lower than the range of the present invention, had low strength, and the separator obtained therefrom had insufficient performance. It is clear that the separator obtained from the precursor sheet obtained in Comparative Example 1-4, in which the content of polyacrylic acid was higher than the range of the present invention, had poor electrical conductivity. It is clear that the separator obtained from the precursor sheet in Comparative Example 1-5, in which the content of particulate phenol resin was less than the range of the present invention, was inferior in gas impermeability. It is clear that the separator obtained from the precursor sheet in Comparative Example 1-6, in which the content of particulate phenol resin was greater than the range of the present invention, had poor electrical conductivity.

Claims

1. The graphite particles include a particulate or fibrous water-insoluble resin, and a water-soluble resin. the content of the water-soluble resin is 0.8 to 18.0 parts by mass relative to 100 parts by mass of the graphite particles, A precursor sheet for a fuel cell separator, wherein the content of the particulate or fibrous water-insoluble resin is 19.0 to 63.0 parts by mass per 100 parts by mass of the graphite particles.

2. 2. The fuel cell separator precursor sheet in accordance with claim 1, wherein the content of the water-soluble resin is 1.0 to 16.0 parts by mass per 100 parts by mass of the graphite particles.

3. 2. The precursor sheet for a fuel cell separator in accordance with claim 1, wherein the content of the particulate or fibrous water-insoluble resin is 20.0 to 60.0 parts by mass per 100 parts by mass of the graphite particles.

4. 2. The fuel cell separator precursor sheet in accordance with claim 1, wherein the graphite particles and the particulate or fibrous water-insoluble resin are fixed by the water-soluble resin.

5. 2. The fuel cell separator precursor sheet according to claim 1, which contains carbon fibers.

6. A fuel cell separator obtained by molding the precursor sheet for a fuel cell separator according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Enzyme power generation device

    JP2020009647A

  • Fuel cell separator and manufacturing method thereof

    JP2020145014A

  • Precursor sheet for fuel cell separator, and fuel cell separator

    JP2023091104A

  • Porous electrode base material and manufacturing method therefor

    WO2016159352A1

  • Manufacturing method of separator for fuel cell

    JP2006269313A